Targeted down-regulation of cytochrome P450 enzymes for forage quality improvement in alfalfa (Medicago sativa L.) - Reddy, M. S. Srinivasa (National Academy of Sciences, 2005)
Improving the digestibility of forages provides a means to enhance animal performance and protect the environment against excessive animal waste. Increased lignin content during maturity, and corresponding changes in lignin composition, correlate with decreased digestibility of forages. These relationships have yet to be investigated in isogenic systems. By targeting three specific cytochrome P450 enzymes of the lignin pathway for antisense down-regulation, we generated transgenic alfalfa lines with a range of differences in lignin content and composition. There was a strong negative relationship between lignin content and rumen digestibility, but no relationship between lignin composition and digestibility, in these transgenic lines. Models for genetic manipulation of forage digestibility based on the changes in lignin composition that increase paper-pulping efficiency in trees are therefore invalid. Down-regulation of 4-coumarate 3-hydroxylase provided the largest improvements in digestibility yet seen in a forage crop.